PENGARUH EXCESS PAYBACK DALAM PENINGKATAN INTENSI INVESTOR PEMULA DALAM BERINVESTASI DI MASA PANDEMI: STUDI EKSPERIMEN - Ida Ayu Purnama; Siti Rokhimah (Universitas Sarjanawiyata Tamansiswa, 2022)
The purpose of this research is to investigate the impact of a bad reputation caused by fraud by a large company on the interest of young investors to invest. In addition, this research also provides a solution to this bad reputation by testing excess pay-back to increase young investors to invest. The method in this research is an experimental study with a 2x2 between subject design. The results show that excess payback can increase the investment interest of young investors in companies that have a bad reputation.